EFFECTS OF DIFFERENT RATES OF ORGANIC AND INORGANINC FERTILIZER ON GROWTH AND YIELD COMPONENTS OF POTATO (SOLANUM TUBEROSUM L.) IN JIMMA ARE, SOUTH WEST ETHIOPIA - Mama, Amana; Jeylan, Jemal; Aseffa, AbebeWoldesenbet (International Journal of Research -GRANTHAALAYAH, 2016)
The experiment was conducted under field condition at Jimma University College of Agricultures and Veterinary Medicine (JUCAVM) to determine the Effects of Different Rate of Organic and Inorganic Fertilizer on Growth and yield Components of Potato (Solanum tuberosumL).The experiment design used was randomized complete block design(RCBD). The experimental treatments were replicated three times. A Potato cultivar ‘Jalene’ was grown combined with Farmyard manure and nitrogen (F0N0), (F20N70), (F0N35),(F0N70), (F20N35), (F20N0) as a treatment.. Data were recorded on Potato leaf area, plant height, leaf length, leaf number, leaf diameter, stem diameter and stem number. The result revealed that the combination of various level of Farmyard manure and nitrogen statistically (p≤0.05) affected leaf area, plant height, leaf length, leaf number, leaf diameter, stem diameter and stem number. The maximum values for leaf area, plant height, leaf length, leaf number, leaf diameter, stem diameter and stem number were recorded from (F0N70, F20N70, F0N70, F20N35, F20N0, F20N70, F20N0) respectively .However The minimum values of all the parameters were recorded from the control treatment (F0 N0). From the study it could be concluded that Potato yield components were greatly affected by different rates of organic and inorganic fertilizers. The appropriate amount of different rates of fertilizers (farmyard manure and nitrogen) should be used to increase Potato growth and yield.